KEKALAHAN AMERIKA PADA PERANG VIETNAM TAHUN 1957-1975: Kekalahan Amerika Pada Perang Vietnam Tahun 1957-1975 - intan vindalia, Junia; Dwi Jayanti, Irma; Seprina, Reka (Krinok: Jurnal Pendidikan Sejarah dan Sejarah, 2024)
This research examines the causes of the United States' defeat in the Vietnam War which took place from 1957 to 1975. The Vietnam War was a result of the Cold War which involved two main ideologies, namely communist ideology and SEATO. The United States, as one of the powers supporting the French colonial government in Indochina, joined the war with the aim of fighting for democratic values and human rights in Vietnam. This research used a qualitative method with a descriptive design and found that several factors that caused the United States to lose the war were the invasion of Vietnam with its large troops and combat equipment, a kind of concern about the domino effect. as well as the existence of ineffective strategies regarding the opposition. The results of this research show that North Vietnam succeeded in achieving victory in the battle and there were several reasons that caused the defeat of the United States and also its influence on the Vietnam War.